THE BURDEN OF HEPATITIS B AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE (ANC) SERVICES IN JUBA TEACHING HOSPITAL (JTH)-JUBA SOUTH SUDAN - Cham, Akway M.; Clever, Sekwat Saviour; Celestino, Rozeta Julio; Clement Thom, Remo Charles Cornelius Eida (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Hepatitis B Virus disease is a major health problem world-wide which causes annual deaths of about 1-34 million indicating that death toll due to Hepatitis B disease is on the rise. It is an infection of the liver that can be self-limiting or if not treated can progress to fibrosis, cirrhosis (scaring) and possibly liver cancer (Hepatocellular carcinoma).